Judith Shapio and Liang Heng, »Cold winds, warm winds. Intellectual life in China today«, Middletown, Connecticut: Wesleyan University Press, 1986, 212 s., 17.95 $. - Stubbe Østergaard, Clemens (Politica, 1987)
-